Occupational heat stress, heat-related effects and the related social and economic loss: a scoping literature review - De Sario, Manuela; de'Donato, Francesca Katherine; Bonafede, Michela; Marinaccio, Alessandro; Levi, Miriam; Ariani, Filippo; Morabito, Marco; Michelozzi, Paola (Frontiers in Public Health, 2023)
Introduction While there is consistent evidence on the effects of heat on workers' health and safety, the evidence on the resulting social and economic impacts is still limited. A scoping literature review was carried out to update the knowledge about social and economic impacts related to workplace heat exposure. Methods The literature search was conducted in two bibliographic databases (Web of Science and PubMed), to select publications from 2010 to April 2022. Results A total of 89 studies were included in the qualitative synthesis (32 field studies, 8 studies estimating healthcare-related costs, and 49 economic studies). Overall, consistent evidence of the socioeconomic impacts of heat exposure in the workplace emerges. Actual productivity losses at the global level are nearly 10% and are expected to increase up to 30–40% under the worst climate change scenario by the end of the century. Vulnerable regions are mainly low-latitude and low- and middle-income countries with a greater proportion of outdoor workers but include also areas from developed countries such as southern Europe. The most affected sectors are agriculture and construction. There is limited evidence regarding the role of cooling measures and changes in the work/rest schedule in mitigating heat-related productivity loss. Conclusion The available evidence highlights the need for strengthening prevention efforts to enhance workers' awareness and resilience toward occupational heat exposure, particularly in low- and middle-income countries but also in some areas of developed countries where an increase in frequency and intensity of heat waves is expected under future climate change scenarios.